Peripheral sphingolipids are associated with variation in white matter microstructure in older adults - Gonzalez, Christopher E. (Neurobiol Aging, 2016)
Sphingolipids serve important structural and functional roles in cellular membranes and myelin sheaths. Plasma sphingolipids have been shown to predict cognitive decline and Alzheimer’s disease (AD). However, the association between plasma sphingolipid levels and brain white matter (WM) microstructure has not been examined. We investigated whether plasma sphingolipids (ceramides, sphingomyelins) were associated with MRI-based diffusion measures, fractional anisotropy (FA) and mean diffusivity (MD), 10.5 years later in 17 WM regions of 150 cognitively normal adults (mean age 67.2). Elevated ceramide species (C20:0, C22:0, C22:1, and C24:1) were associated with lower FA in multiple WM regions, including total cerebral WM, anterior corona radiata, and the cingulum of the cingulate gyrus. Higher sphingomyelins (C18:1, C20:1) were associated with lower FA in regions such as the anterior corona radiata and body of the corpus callosum. Furthermore, lower sphingomyelin to ceramide ratios (C 22:0, C24:0, C24:1) were associated with lower FA or higher MD in regions including the superior and posterior corona radiata. However, while these associations were significant at the a priori p<0.05, only associations with some regional diffusion measures for ceramide C22:0 and sphingomyelin C18:1 survived correction for multiple comparisons. These findings suggest plasma sphingolipids are associated with variation in WM microstructure in cognitively normal aging.